Synergistic Effect of Antibiotics and Enzymes as Strategies For Combating Biofilm Formation By Pseudomonas Aeruginosa Pao1 - Komal Sharma; Abhishek Prajapati; Mansi Shukla; Shilpa Gupte (International Journal of Pharma and Bio Sciences, 2020)
Biofilms are surface attached communities of bacteria, fungi, protozoa, and many other microorganisms. Potential biofilm formers are known as “ESKAPE'' which includes Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacter aerogenes . Among them, Pseudomonas aeruginosa is considered as the most health injurious biofilm forming organism that causes nosocomial infections like ventilator associated pneumonia, chronic wound infections, chronic rhinosinusitis etc. Efficient removal of biofilm from medical devices is a big challenge to avoid hospital acquired infections as these devices are delicate and cannot be reprocessed using harsh chemicals or high temperature. Therefore, use of mild solutions for removal of biofilm is advisable. In the present study, Pseudomonas aeruginosa PAO1 acted as potential biofilm former with 10% inoculum size in TSB medium. The biofilm of P.aeruginosa PAO1 was studied microscopically and the results revealed that with time the number of cells increased and thick biofilm formation was observed with more Exopolysacharide production. Susceptibility of P. aeruginosa PAO1 against some antibiotics and enzymes were analyzed individually as well as in combinations using microtiter plate. The efficiency of antibiotics to eradicate biofilm was higher than the enzymes but the use of antibiotics alone required higher concentration to eradicate biofilm. While combination of enzymes and antibiotics can eradicate the biofilm at sub minimal concentration as well as that can minimize the load of antimicrobials in the environment. Therefore, in this study when combination of ciprofloxacin at sub MIC of 1.56 µg/ml was applied with lysozyme and protease, 68±0.5% and 56±0.6% biofilm eradication were observed, respectively but only 40±0.5% eradication was observed when treated with ciprofloxacin alone. Similarly, when combination of levofloxacin at sub MIC of 6 µg/ml was applied with DNase, 95% eradication was observed while only 32±0.8% eradication was observed when treated with levofloxacin alone.